Analisis gaya belajar siswa dalam pembelajaran tematik selama masa Pandemi Covid-19 di kelas Va SD Muhammadiyah Karangharjo Sleman - Anugrah Lintang Pratista; Dwi Wijayanti (Universitas Sarjanawiyata Tamansiswa, 2023)
This study aims to identify what learning styles are being used by Class Va students and to find out the impact of thematic learning on student learning styles during the Covid-19 pandemic at SD Muhammadiyah Karangharjo. This research method is qualitative with a cross-sectional survey approach. The data sources in this study are primary data sources and secondary data sources. The variables in this study were the student's learning styles in thematic learning of Class VA. The data collection methods used were observation, interviews, and documentation. The data validity techniques used in this study are source triangulation, technique triangulation, and time triangulation. The data analysis techniques used in this study are data collection, data reduction, data presentation, and conclusion drawing. The results of the study are that there are three types of student learning styles in class VA based on the results of the observation survey, namely Visual learning styles 66.67%, Auditory learning styles having a percentage of 14.28%, and Kinesthetic learning styles with a percentage of 19.04%. With the large percentage contained in the diagram above, it can be seen that the common learning style of Class VA SD Muhammadiyah Karangharjo students is Visual Learning Style and with the large amount of material contained in thematic learning, students prefer to pay attention to the teacher who is thematically explaining their learning material.